Xpert Flu as a rapid diagnostic test for respiratory tract viral infection: evaluation and implementation as a 24/7 service. Issue 2 (1st February 2018) - Haglund, Sofie; Quttineh, Maysae; Nilsson Bowers, Annette; Matussek, Andreas; Henningsson, Anna J.
Abstract: A rapid and reliable influenza method is important to meet diagnostic needs. Here, the performance of the cartridge-based Xpert Flu assay was evaluated in comparison with an in-house real-time PCR method. Analysis was then decentralized from the clinical microbiology laboratory located at County Hospital Ryhov, Jönköping, Sweden, to the clinical chemistry laboratories present at the three hospitals in Region Jönköping County, allowing a 24/7 service. In total, 189 clinical samples were included in 2014–2015. The overall sensitivity and specificity of Xpert Flu were both 99%. With Xpert Flu and the 24/7 service the median turn-around time from sampling to available test result decreased from 22 h in 2013 to 1.9 h in 2015. In summary, the analytical performance of Xpert Flu is excellent. The large degree of automation of GeneXpert and Xpert Flu with assay on demand has allowed a 24/7 service at the clinical chemistry laboratories in the county, and a significantly reduced turn-around time, which is valuable for both patients and the healthcare providers.